PENGARUH MOTIVASI DAN BIAYA PENDIDIKAN TERHADAP MINAT MAHASISWA MENGIKUTI PENDIDIKAN PROFESI AKUNTANSI ( PPAk ) - Pratama, Rizka Ananda (Universitas YPPI Rembang, 2022)
The purpose of this study was to determine the effect of motivation and education costs on student interest in taking the Accounting Profession Education (PPAk) at Private Universities in the city of Palembang. In this study, the variables of career motivation (X1), economic motivation (X2), and education costs (X3) were used. Data was collected by distributing online questionnaires to 12 private universities in the city of Palembang. Samples were taken using the proportionate stratified random sampling method with the Arikunto formula. The number of samples used is 151 respondents. This study uses SPSS version 26 to manage the data. Based on the t test, the significance of career motivation is 0.003 < 0.05, economic motivation is 0.003 < 0.05, and education costs are 0.106 < 0.05. The results of this study partially show that career motivation and economic motivation affect student interest in PPAk, while education costs have no effect on student interest in PPAk. Keywords: Career Motivation, Economic Motivation, Cost of Education, and Student Interest in Participating in Accounting Profession Education (PPAk).